REVITALIZING POETRY LEARNING: ENHANCING STUDENT OUTCOMES THROUGH THE DEMONSTRATION METHOD IN SIXTH GRADE - Andi Wapa; Denok Andini; Ulya Nurul Laili (Consilium: Education and Counseling Journal, 2026)
This research aims to improve students' learning outcomes in reading poetry through the application of demonstration methods in class VI. The background to this research is the low ability of students to read poetry expressively, caused by conventional learning methods that do not involve students' liveliness. This research uses a Class Action Research (PTK) approach with two cycles, each consisting of planning, implementation, observation and reflection stages. The research subjects were 16 students with varying levels of ability. The results of the pre-cycle observations showed that the majority of students were in the category of sufficient and insufficient grades, with an average of 59.37. After the application of the demonstration method, there was a significant increase in cycle I with the average value reaching 73.43. Students experience development in terms of intonation, expression, articulation, and appreciation when reading poetry. In addition to improving technical skills, this method also has a positive impact on students' learning motivation and self-confidence. The results of the study concluded that the demonstration method was effectively used in learning to read poetry because it was able to integrate cognitive, affective and psychomotor aspects. Therefore, this method is recommended to be applied in the teaching of other literary materials that require the expressive and interpretive involvement of students directly.